Functional characterization of Borrelia spielmanii outer surface proteins that interact with distinct members of the human factor H protein family and with plasminogen - Seling, Annekatrin; Siegel, Corinna; Fingerle, Volker; Jutras, Brandon L.; Brissette, Catherine A.; Skerka, Christine; Wallich, Reinhard; Zipfel, Peter F.; Stevenson, Brian; Kraiczy, Peter (Infection and immunity, 2010)
Acquisition of complement regulator factor H (CFH) and factor H-like protein 1 (CFHL1) from human serum enables Borrelia spielmanii, one of the etiological agents of Lyme disease, to evade complement-mediated killing by the human host. Up to three distinct complement regulator-acquiring surface proteins (CRASPs) may be expressed by serum-resistant B. spielmanii, each exhibiting an affinity for CFH and/or CFHL1. Here, we describe the functional characterization of the 15-kDa CRASPs of B. spielmanii, members of the polymorphic Erp (OspE/F-related) protein family, that bind two distinct host complement regulators, CFH and factor H-related protein 1 (CFHR1), but not CFHL1. CFH bound to the B. spielmanii CRASPs maintained cofactor activity for factor I-mediated C3b inactivation. Three naturally occurring alleles of this protein bound CFH and CFHR1 while a fourth natural allele could not. Comparative sequence analysis of these protein alleles identified a single amino acid, histidine-79, as playing a significant role in CFH/CFHR1 binding, with substitution by an arginine completely abrogating ligand binding. The mutation of His-79 to Arg did not inhibit binding of plasminogen, another known ligand of this group of borrelial outer-surface proteins.
Published ahead of print on 26 October 2009
Gesehen am 19.05.2021